The Effect of Information Recycling Strategy on The Acquisition of Rhetorical Concepts Among Fourth-Grade Literary Students (Journal of the College of Basic Education, 2025)
This study aimed to determine " The effect of information recycling strategy on the acquisition of rhetorical concepts among fourth-grade literary students." To achieve this, the hypothesis was formulated: "There is no statistically significant difference at a significance level of 0.05 between the average scores of students in the experimental group who were taught using the recycling strategy and students in the control group who were taught using the traditional method in the rhetorical concepts acquisition test." The researcher used the experimental design with partial control. Therefore, the researcher deliberately chose Zuhair Ibn Abi Salma Intermediate School to implement the experiment, and the research sample was determined to be (67) students. The experiment continued for a full semester and ended with a post-test of acquiring rhetorical concepts. The researcher concluded that following the rotation strategy in teaching plays a positive role in acquiring rhetorical concepts in rhetorical topics compared to the traditional method currently followed.